2020
DOI: 10.1007/s40121-020-00289-3
|View full text |Cite|
|
Sign up to set email alerts
|

Paediatric Recurrent Ear, Nose and Throat Infections and Complications: Can We Do More?

Abstract: Recurrent respiratory tract infections (rRTIs), of which there are three main groups-otitis media, tonsillitis and sinusopathies-are very common in paediatric populations and are associated with significant morbidity and mortality due to complications. These infections substantially reduce quality of life for paediatric patients and their families and are a significant personal, medical and economic burden on the patients, the patients' families and the healthcare system. Most rRTIs are of viral origin; howeve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 49 publications
0
24
0
1
Order By: Relevance
“…OM-85 is a lysate of 21 strains of bacterial pathogens derived from the eight major species and sub-species that are a common cause of RTIs (Haemophilus influenzae, Streptococcus pneumoniae, Klebsiella pneumoniae, Klebsiella ozaenae, Staphylococcus aureus, Streptococcus pyogenes Streptococcus viridans, Moraxella catarrhalis) [ 19 ]. Several studies have shown that both innate and adaptive immunity are strongly influenced by OM-85 [ 50 , 51 , 52 , 53 , 54 ]. Oral OM-85 administration stimulates dendritic cell maturation in gastrointestinal Peyer’s patches, resulting in the increase of the immune defenses also in the lung mucosa [ 19 ].…”
Section: Immunotherapymentioning
confidence: 99%
See 1 more Smart Citation
“…OM-85 is a lysate of 21 strains of bacterial pathogens derived from the eight major species and sub-species that are a common cause of RTIs (Haemophilus influenzae, Streptococcus pneumoniae, Klebsiella pneumoniae, Klebsiella ozaenae, Staphylococcus aureus, Streptococcus pyogenes Streptococcus viridans, Moraxella catarrhalis) [ 19 ]. Several studies have shown that both innate and adaptive immunity are strongly influenced by OM-85 [ 50 , 51 , 52 , 53 , 54 ]. Oral OM-85 administration stimulates dendritic cell maturation in gastrointestinal Peyer’s patches, resulting in the increase of the immune defenses also in the lung mucosa [ 19 ].…”
Section: Immunotherapymentioning
confidence: 99%
“…Moreover, OM-85 stimulates antimicrobial peptide release and the activation of macrophages with the increased secretion of antiviral cytokines and chemokines such as IFN alpha and beta. Finally, B cell-activating cytokines are produced with increases in both serum and mucosal polyclonal immunoglobulins (IgG and IgA) [ 50 , 51 , 52 , 53 , 54 ].…”
Section: Immunotherapymentioning
confidence: 99%
“…Recurrent respiratory tract infections (RRTIs) are a leading cause of morbidity and mortality in children and adults (1,2). While many of the RRTIs are of viral origin, antibiotics are often misused in these conditions leading to bacterial resistance and microbiota disruption (3)(4)(5).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, implementation of effective strategies to improve their management has become a therapeutic challenge (6). An increasing number of studies are focused on prophylactic and therapeutic interventions that enhance the body's natural defenses against infections and/or downregulate the accompanying harmful inflammatory process (2,7). Mucosal immunotherapy with bacteria-derived products or whole cell bacteria may play that role.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation